Traditional Games and the Sri Lankan Culture; Reflection of Traditional Games as a Component of Implicit Culture of Sri Lanka - H P N, Perera (International Journal of Scientific Research and Management (IJSRM), 2023)
Traditional games are still preserved in Sri Lankan context since it acts as a major role in Sinhala new-year season.  However, the vicinity of the traditional games such as Eluwan keema (catching of goats/Goats Play), and Gudu paneema (Tip-cat game) are gradually declining due to the inception of new games for the Sinhala New Year festival by unanimous people for different objectives. Traditional games have been so far identified as a reflection of explicit culture and therefore, the main aim of the study was to understand the relationship between traditional games and culture and to reveal whether the said is a sub-section of implicit culture with the use of prevailing literature. The main concentration of this research was given to present the cultural background of traditional games created by the mindsets of our forefathers and to understand the blend of implicit and explicit cultural knowledge that guided such activities. Thorough observations of traditional games played by different parties were also observed by the researcher to narrate the implicit cultural values embedded in such games. Literature reveals that playing a game is explicit but molding a game is part of the implicit culture. Traditional games are evolved throughout the years from their inception and had changed the basics from time to time. Changes include the costumes of the participants, the equipment used, and the objective of playing such games. In-depth interviews were conducted with fifteen elderly villages. The results of this study synthesized through observation, interviews, and secondary data review established that it can be treated that the traditional games of Sri Lanka as the reflection of components of implicit and explicit culture.